Kajian Evaluasi Pelayanan Kajian Evaluasi Pelayanan Kesehatan Jiwa Pada Kelompok Rentan Berbasis Kecamatan di Daerah Istimewa Yogyakarta - Suhada, Reza Iqbal; Anggraeni, Jatu (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2025)
Background: Mental health is a crucial aspect of overall human health. The WHO reported that more than 700 million people worldwide experienced mental disorders in 2020, with depression and anxiety being the most common. Mental health is a multidimensional issue that requires comprehensive interventions, ranging from government policies and public education to capacity building for health workers. Methods: This research method uses descriptive analytic. The study instrument was used to collect primary data from various community health centers and sub-districts throughout Yogyakarta Special Region (DIY). Secondary data was also obtained from all health and social service offices. Focus group discussions (FGDs) were also conducted with community health center and sub-district officers. A total of 53 respondents to obtain direct information regarding mental health services in each region. The study was conducted for approximately two months, from October 10, 2025, to December 10, 2025. Quantitative descriptive analysis was used in this study. Results: Most regions lack adequate mental health service facilities, including the availability of necessary facilities and infrastructure. Each district/city in Yogyakarta Special Region (DIY) has a relatively similar pattern of vulnerable groups dominating. Vulnerable groups at the sub-district level are not evenly distributed. The concentration of certain groups in specific areas underscores the importance of a spatial targeting approach in social welfare program planning. Based on the average score, Sleman Regency and Yogyakarta City are in the Good category, while Bantul, Kulon Progo, and Gunungkidul Regencies are in the Fair category.Conclusion: Strengthening synergy between agencies (sub-districts and sub-districts/kemantren) and collaborating with the community are crucial to addressing these vulnerable groups at risk of mental health problems. A data-driven approach and periodic territorial-based evaluations will determine more adaptive health service policies to the community's mental health conditions.